(untitled) (Revista Brasileira Multidisciplinar, 2026)
This article reviews the chemical and biological properties of the species Cecropia pachystachya, highlighting its traditional use, proven biological effects, and toxicity. The species, widely used in folk medicine, presents a variety of phytochemical constituents, including phenolic derivatives, flavonoids, and organic acids, which are responsible for its biological activities, such as antioxidant, gastroprotective, and potential anti-inflammatory actions. Despite several reported therapeutic activities, some traditional practices have not been validated in laboratory assays, indicating the need for further research to explore the plant’s therapeutic potential fully. Thus, a bibliographic search was conducted between January and September 2024, using the species name (Cecropia pachystachya Trécul) and its synonyms as search descriptors. Additionally, the review emphasizes that some properties identified in C. pachystachya are not mentioned in traditional use, suggesting that scientific research may reveal new uses and applications for this species. This study serves as a basis for future investigations, aiming to promote new therapeutic alternatives derived from plants.